Pembuatan Simulasi 3D Virtual Reality Berbasis Android Sebagai Alat Bantu Terapi Acrophobia - Ghali Adyo Putra; Rinta Kridalukmana; Kurniawan Teguh Martono (Jurnal Teknologi dan Sistem Komputer, 2017)
Virtual Reality is three-dimensional technology and developing rapidly at the moment. Therefore, Virtual Reality technology implementation will be useful for people. One of this implementation is in clinical fields, which is for handling phobia. One of the therapies provided by a therapist to patients is by using flooding technique that faces the patient in the situation that confronts the making of fear until no longer feel anxious. In some cases, the flooding technique for acrophobia almost impossible because of the level of dangerous and the expensive cost. By using game engine Unity and Multimedia Development Life Cycle (MDLC) method which has six stages, concept, design, material collection, assembly, testing, and distribution, application development Android-based Virtual Reality will resolve the issue. Based on the results of Black-box method, functions from the application of virtual reality simulation as a tool for the treatment of acrophobia has already worked well. Further research is needed to find out the impact of application in the medical sector.